2022
DOI: 10.1001/jamanetworkopen.2022.6920
|View full text |Cite
|
Sign up to set email alerts
|

Association of Subcutaneous or Intravenous Administration of Casirivimab and Imdevimab Monoclonal Antibodies With Clinical Outcomes in Adults With COVID-19

Abstract: Key Points Question Is subcutaneous treatment with casirivimab and imdevimab associated with improved 28-day clinical outcomes compared with nontreatment, and is it clinically similar to intravenously administered casirivimab and imdevimab for outpatients with COVID-19? Findings In this cohort study of 1959 propensity-matched outpatients with mild to moderate COVID-19 symptoms, the 28-day rate of hospitalization or death was 3.4% vs 7.0% for those receiving… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 9 publications
6
21
0
Order By: Relevance
“…To date, there are only a modest number of case reports/series in the literature where mAbs for treatment of COVID have been used in IMID patients with or without B cell depleting agents ( Table 2 ). Similar to our case, these cases also showed favorable outcomes with no safety concerns ( 13 17 ). Yetmar et al ( 16 ) and McCreary et al ( 17 ) have reported the largest case series of treatment with mAbs in immunocompromised patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To date, there are only a modest number of case reports/series in the literature where mAbs for treatment of COVID have been used in IMID patients with or without B cell depleting agents ( Table 2 ). Similar to our case, these cases also showed favorable outcomes with no safety concerns ( 13 17 ). Yetmar et al ( 16 ) and McCreary et al ( 17 ) have reported the largest case series of treatment with mAbs in immunocompromised patients.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our case, these cases also showed favorable outcomes with no safety concerns ( 13 17 ). Yetmar et al ( 16 ) and McCreary et al ( 17 ) have reported the largest case series of treatment with mAbs in immunocompromised patients. In the work of Yetmar et al, four different mAbs reduced hospitalization rates, mortality rates and persistent infections in 180 patients who received B cell depleting therapy ( 16 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The reduction of hospitalization rate with our combination therapy (74%) was better than that of inhaled corticosteroids (36%) (40) and molnupiravir (51%) (41). Although there are other medications such as nirmatrelvir (89%) (42), remdesivir (86%) (43), Paxlovid (88%) (44), and the monoclonal antibodies (70 – 85%) (7,45-47) with slightly better outcomes, the results may not be directly comparable. For example, on average, our patients are sicker than the patients treated with nirmatrelvir, remdesivir, and Paxlovid; this is based on maximum number of days elapsed since symptom onset for eligibility to be part of trials for remdesivir (within 7 days) (43), nirmatrelvir (within 3 days) (42), and Paxlovid (within 5 days) (44).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] A small minority of patients received subcutaneous casirivimab and imdevimab to accommodate surging patient referrals and staffing shortages. 20 From December 23, 2021 through January 21, 2022, all patients received intravenous sotrovimab due to the emergence of the Omicron variant. Starting September 28, 2021, pregnant patients and patients with immunocompromised conditions were given priority for mAb treatment due to drug scarcity.…”
Section: Methodsmentioning
confidence: 99%